What it takes to win: examining predicted versus actual swimming performances at the Paris 2024 Olympic Games, and what comes next - Powell, C; Pyne, D; Crowley, E; Mujika, I. (International Journal of Sports Physiology and Performance, 2025)
Predictions of performances should be evaluated to confirm their accuracy. Work by this group has resulted in 3 sets of predictions being generated for swimming events at the Paris 2024 Olympic Games, using the same statistical approach for each set.